A Practical Approach to Nutrition, Protein-Energy Wasting, Sarcopenia, and Cachexia in Patients with Chronic Kidney Disease - Hanna, Ramy M.; Ghobry, Lena; Wassef, Olivia; Rhee, Connie M.; Kalantar-Zadeh, Kamyar (Blood purification, 2020)
Objectives of Review: Protein-energy wasting (PEW) is a state of disordered catabolism resulting from metabolic and nutritional derangements in chronic disease states. Patients with chronic kidney disease (CKD), and end-stage renal disease (ESRD) in particular, have muscle wasting, sarcopenia, and cachexia that contribute to frailty and morbidity. Moreover, reverse epidemiology findings have strongly linked PEW with mortality in CKD and ESRD. Updated Findings: The malnutrition-inflammation score (KALANTAR Score) provides a useful tool to predict nutritional risk. A stronger focus on renal nutrition in renal patients is needed to attenuate cachexia and muscle loss. Malnutrition is a far greater threat in patients with renal disease than obesity, which means dietary counseling needs to be tailored to reflect this observation. The need to achieve optimal caloric intake is compounded by the need to limit excess protein intake in CKD, resulting in the need for energy supplementation to avoid PEW. Preventing PEW is the most pressing clinical concern in CKD/ESRD. Other nutritional issues to reckon in renal disease include the need to normalize serum bicarbonate to manage acidosis, uric acid control, and phosphorous control in CKD and ESRD. Exercise maybe beneficial, but further work is needed to prove a conclusive benefit via a randomized trial. Summary: PEW prevention is an integral part of renal nutrition and is of paramount importance given the obesity paradox. Integrative approaches by physicians and dieticians are needed to take a holistic view of a patient’s diet beyond just control of particular laboratory parameters.